2006
DOI: 10.1021/jf0527706
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin Production in the Maize Pathogen Fusarium verticillioides:  Genetic Basis of Naturally Occurring Chemical Variation

Abstract: Fumonisins are polyketide-derived mycotoxins produced by the maize pathogen Fusarium verticillioides. Previous analyses identified naturally occurring variants of the fungus that are deficient in fumonisin C-10 hydroxylation or that do not produce any fumonisins. In the current study, gene deletion and genetic complementation analyses localized the C-10 hydroxylation deficiency to a cytochrome P450 monooxygenase gene in the fumonisin biosynthetic gene (FUM) cluster. Sequence analysis indicated that the hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 34 publications
6
78
0
3
Order By: Relevance
“…A PCR assay with two sets of primers revealed that all F. verticillioides possessed the FUM1 gene. This result is concordant with other studies that established F. verticillioides as a potent fumonisin producer (Proctor et al, 2006). Also F. proliferatum and F. fujikuroi are fumonisin producers and F. andiyazi was shown to produce only trace amounts of fumonisin (Leslie et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…A PCR assay with two sets of primers revealed that all F. verticillioides possessed the FUM1 gene. This result is concordant with other studies that established F. verticillioides as a potent fumonisin producer (Proctor et al, 2006). Also F. proliferatum and F. fujikuroi are fumonisin producers and F. andiyazi was shown to produce only trace amounts of fumonisin (Leslie et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that one of these genes could have been inactivated or deleted in the fumonisin nonproducing wheat isolate MRC 7884. Similarly, strains lacking FB 2 and/or FB 3 could be lacking the activity of the FUM2 and/or FUM3 proteins, as FUM2 and FUM3 deletion mutants were shown to only produce FB 2 and FB 4 , and FB 3 and FB 4 , respectively [8,32]. The fumonisin B profiles where at least two different profiles were observed, support the other results in this study that the maize and wheat isolates are not the same species.…”
Section: Discussionsupporting
confidence: 85%
“…Also, strains lacking FUM2 produced only fumonisin analogues (FB2 and FB4) that lack the C-10 hydroxyl group [32], and FUM3 deletion mutants produce only analogues (FB3 and FB4) that lack the C-5 hydroxyl group [8]. The individual deletions of the remaining FUM genes resulted in various effects and influences on fumonisin production [6-9, 30, 48], including no effects on fumonisin accumulation with the deletions of FUM15, FUM16, FUM17 or FUM18 [9,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Southern analysis of endophyte strains for ltmC, ltmM, ltmP, and ltmJ genes. Southern analysis of EcoRI-digested genomic DNA hybridized with 32 P-labeled probes (Table 3) However, in some cases, a lack of secondary metabolite production correlated with little or no gene expression and/or sequence variations within the coding and promoter regions of genes within the cluster, which can result in naturally occurring pathway variants (21,(33)(34)(35)53). The LTM locus from the Epichloë and Neotyphodium species we screened contain examples of gene absence (partial or complete cluster) and in three cases, sequence variation in a gene (ltmF and ltmE) that blocks or alters the encoded biosynthetic step.…”
Section: Discussionmentioning
confidence: 99%